Problems Of Teaching Phraseology (By The Example Of The Textbook Russian Phraseology For Poles) - Невзорова-Кмеч, Елена (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
This article is devoted to one of the questions in the teaching methods of Russian as a foreign language for Poles, namely, the teaching problems of Russian idioms. The main goal of this work was to determine expediency and effectiveness of learning phraseology by foreign students. In order to achieve it, we studied some textbooks on Russian for Poles, their structure, content, we identified methods, principles, ways of introducing phraseological material into them. The main attention is paid to the Russian phraseology for Poles (Walter, Mokienko et al. 2018). We analyzed the results of using phraseology in Russian language classes for Polish students.